2020
DOI: 10.1111/febs.15461
|View full text |Cite
|
Sign up to set email alerts
|

USP28 and USP25 are downregulated by Vismodegib in vitro and in colorectal cancer cell lines

Abstract: Deubiquitinase USP28 plays a crucial role in tumorigenesis by enhancing the stabilities of multiple cancer‐related proteins including c‐Myc, Notch1, and LSD1, and has become an attractive target for anticancer drug development. However, to date, only a few of USP28‐targeted active compounds have been developed, and the active compound‐binding pocket in USP28 has not been experimentally revealed yet. In this study, bioassay‐based high‐throughput screening was applied to discover USP28‐targeted inhibitors from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…Inhibitors targeting the MYC degradation pathway.Vismodegib, a sonic hedgehog inhibitor used for the treatment of basal cell carcinoma, was recently shown to bind to USP28 and inhibit its DUB activity(101). Vismodegib exhibits selectivity towards USP28 and its evolutionally related USP25.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitors targeting the MYC degradation pathway.Vismodegib, a sonic hedgehog inhibitor used for the treatment of basal cell carcinoma, was recently shown to bind to USP28 and inhibit its DUB activity(101). Vismodegib exhibits selectivity towards USP28 and its evolutionally related USP25.…”
mentioning
confidence: 99%
“…Vismodegib exhibits selectivity towards USP28 and its evolutionally related USP25. Treatment of cancer cells with Vismodegib reduces the levels of c-Myc and Notch1 and suppresses cell growth(101). In addition, lanatoside C, a cardiac glycoside, has been shown to reduce MYC levels and suppress gastric cancer cell proliferation by inhibiting USP28 binding to MYC, thereby destabilizing MYC, although it remains to be determined whether lanatoside C directly targets USP28(102).Given that SENP1 positively regulates MYC levels and activity, SENP1 is an interesting cancer therapeutic target.…”
mentioning
confidence: 99%
“…Benzylaminoethanols (AZ1–AZ4) were the first reported compounds to directly and effectively target USP28 [ 29 ]. More recently, a few synthesized USP28 inhibitors were also reported [ 30 , 31 ]. To the best of our knowledge, streptoglutarimide H is the first USP28 inhibitor found from natural resource to display potent antiproliferative activity against lung cancer cells with unique mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al found that this inhibition suppressed the expression levels of its related substrate proteins, including c-Myc, Notch1 and tankyrase-1/2 in vitro and in colorectal cell lines. The binding pocket for vismodegib in USP25 is within two helices that span Asp262 to Glu285 and Asn293 to Tyr300 ( Wang et al, 2020a ).…”
Section: Development Of Inhibitors Of Usp25mentioning
confidence: 99%